Strategi Digital Marketing untuk Generasi Muda Studi Kasus: Applikasi Spotify di Indonesia - Anita Agustina Wulandari; Octavia Dwi Xenora; Aulia Afniar Rahmawati (DIGICOM : Jurnal Komunikasi dan Media, 2025)
This research will outline several Spotify digital marketing strategies in Indonesia and evaluate the effectiveness of this approach in increasing brand awareness and customer loyalty, especially among the younger generation. Through Spotify case study analysis, we will see how digital marketing plays an important role in strengthening a brand's position in the competitive music streaming industry. The author is interested in conducting research on digital marketing strategies using media to reach young people. Through various options such as the online format in the Spotify For Brands feature and using the power of the Spotify application in Indonesia. It is felt that research on the Spotify streaming music application is very important to do at this time, considering that references to Spotify are still dominated by Generation Z and Millennial Generation. This research uses a qualitative descriptive approach with a data collection method that involves taking data from the library, reading, taking notes and processing research materials. Next, the data obtained is poured into appropriate sub-chapters to answer the research problem formulation. Based on the analysis of Spotify's digital marketing strategy which is based on behavioral intention, it can be concluded that this approach is very effective in increasing brand awareness and loyalty among Indonesia's young generation. Spotify leverages a combination of data analytics and a deep understanding of user behavioral intent to provide content that is relevant and engaging for each individual.